Lost in Transmission? Stock Market Impacts of the 2006 European Gas Crisis - Ulrich Oberndorfer; Dirk Ulbricht (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
Around the turn of the year 2005/2006, the Russian freezing of natural gas exports to the Ukraine led to a European gas crisis. Using event study technique, we first investigate whether the Russian announcement of suspension of gas deliveries, this suspension itself as well as its withdrawal, had an effect on unsystematic volatility of European energy stocks. Secondly, we measure event effects on stock returns, taking volatility into account. Our results suggest that the announcement of the crisis and therefore a rise of Western Europe?s energy cost and risk tended to increase market expectations with respect to energy-related firms. In contrast, market uncertainty increased when Russia reopened its valves. One reason for these findings could be windfall profits of energy-related companies due to increasing resource and electricity prices. The existence of event-induced volatility confirms our methodological approach in order to test for abnormal returns.
Keywords: G14; Q43; Q41; 330; energy security; event study; gas crisis